Bag-ong Kinabuhi sa yutang banyaga formation of Cebuano community in Baybay, Miag-ao, Iloilo - Lumanog, Valerie M.
This is a study about the formation of a Cebuano community in Baybay, Miagao in Panay Island composed of Cebuano-speaking migrants from Calatrava, Negros Occidental. This study looks into the factors behind such migration by discussing their reasons for coming to Miag-ao. this study likewise, tackles the economic and social adaptations that the migrants underwent in their new environment., Most of the materials that the researcher used in this study are those regarding migration and its effects on the social and economic life of a migrant in a new environment. the materials used are found in the UPV Main Library, Center for West Visayan Studies (CWVS) in Iloilo City and in the Cebu City Public Library. Most of the data gathered and used are from the interviews conducted by the researcher on the migrants and other knowlegeable individuals. The researcher also spent some ample time in the community studied itself. Based on the data gathered, the reasons for migrating to Miag-ao by the Cebuanos from Calatrava are basically economic in nature. All of them cited, the hope for a better life, the attraction of a bountiful catch and to end hardships working in sugarcane plantation among others as the factors which influenced them to migrate to Miag-ao. This study was able to found out that the community mainly strives on fishing and boat building which was also their source of livelihood way back in Calatrava aside from sugarcane plantation laborers. The difference is that, only this time the community made fishing and boat building as their main source of livelihood and they are no longer working as laborers in sugarcane plantations. Aside from fishing and boat building, the community also engages in selling fish in the market, barter, raising livestock and putting their own sari-sari store. This study was also able to find out that since the coming of the first migrant in 1963, the Cebuanos in the community established social ties with the Karay-as which, is one of the manifestations of how these migrants socially adjust to their new environment. Some of these social ties that the Cebuanos established with the Karay-as are through intermarriages and through the Kumare-Kumpare system. Through this, the Cebuanos and the Karay-as share a kinship network which are consaguinal, affinal and lastly ritual in nature which helped in the strengthening of such community as seen in the number of years of stay of the said Cebuanos in Miag-ao. To sum up, this study looks into the phenomenon of the formation of a Cebuano community in a non-Cebuano-speaking area and how its members were able to strengthen such formation. Lastly, this study offers a step for further investigation of the said phenomenon.